(untitled) (American Journal of Islam and Society, 2004)
Islam and Dhimmitude is an attempt to confute the concept of “protected minority” (under which Islamic civilization established what was, up to its time, the most successful model of pluralistic society) with the worst aberrations from that model. The subtitle “Where Civilizations Collide” indicates how the author expects her polemic to serve the current wave of neoimperialism. The book seeks to recruit Christians in support of the Zionist project by explaining away Christian expressions of appreciation of Muslim tolerance as a false consciousness inspired by a self-hatred she calls dhimmitude, meaning a state of mind that acquiesces, even promotes, the victim’s own subjugation. The book’s first half is devoted to proposing a paradigm in which Qur’anic verses in favor of human rights are ignored, official acts to the benefit of dhimmis are brushed off as machinations to breed resentment between dhimmi groups, and injustices against Muslims are figments of the imagination invented to whitewash the Islamic master plan for subjugating the non-Islamic world into a state of dhimmitude. The second half works within this paradigm to vilify Christian anti-Zionists (including Europeans as well as Arabs) as dhimmi pawns of Muslim oppressors. (Curiously, she does not attempt to dismiss Jewish critics of Israel in the same manner.) ...